Patient and Provider Perceptions of a Patient Navigation Program to Improve Postpartum Care Among Publicly Insured Women - Hu, Fengling; Strohbach, Angelina; Martinez, Noelle G.; Simon, Melissa A.; Yee, Lynn M. (American Journal of Perinatology, 2019)
Objective This study was aimed to assess patient and provider perceptions of a postpartum patient navigation program.Study Design This was a mixed-method assessment of a postpartum patient navigation program. Navigating New Motherhood (NNM) participants completed a follow-up survey including the Patient Satisfaction with Interpersonal Relationship with Navigator (PSN-I) scale and an open-ended question. PSN-I scores were analyzed descriptively. Eighteen provider stakeholders underwent in-depth interviews to gauge program satisfaction, perceived outcomes, and ideas for improvement. Qualitative data were analyzed by the constant comparative method.Results In this population of low-income, minority women, participants (n = 166) were highly satisfied with NNM. The median PSN-I score was 45 out of 45 (interquartile range [IQR]: 43–45), where a higher score corresponds to higher satisfaction. Patient feedback was also highly positive, though a small number desired more navigator support. Provider stakeholders offered consistently positive program feedback, expressing satisfaction with NNM execution and outcomes. Provider stakeholders noted that navigators avoided inhibiting clinic workflow and eased clinic administrative burden. They perceived NNM improved multiple clinical and satisfaction outcomes. All provider stakeholders believed that NNM should be sustained long-term; suggestions for improvement were offered.Conclusion A postpartum patient navigation program can perceivably improve patient satisfaction, clinical care, and clinic workflow without burden to clinic providers.
Keywords: navigator; patient navigation; postpartum; program evaluation; stakeholder feedback